COVID-19 vaccination perceptions and intentions of maternity care consumers and providers in Australia - Zoe Bradfield (Public Library of Science (PLoS), 2021)
Introduction Vaccination against COVID-19 is a key global public health strategy. Health professionals including midwives and doctors support and influence vaccination uptake by childbearing women. There is currently no evidence regarding the COVID-19 vaccination perceptions and intentions of those who receive or provide maternity care in Australia. The aim of this study was to address this gap in knowledge and explore the perceptions and intentions regarding COVID-19 vaccination from consumers and providers of maternity care in Australia. Methods A national cross-sectional online study conducted in early 2021 in Australia, a country that has had a very low number of COVID-19 cases and deaths. Recruitment was undertaken through parenting and health professional social media sites and professional college distribution lists. A total of 853 completed responses, from women (n = 326), maternity care providers including doctors (n = 58), midwives (n = 391) and midwifery students (n = 78). Findings Personal intention to be vaccinated ranged from 48–89% with doctors most likely and women least likely. Doctors and midwifery students were significantly more likely to recommend the vaccine to pregnant women in their care than midwives (p<0.001). Fewer doctors (2%) felt that women should wait until breastfeeding had concluded before being vaccinated compared with 24% of midwives and 21% of midwifery students (p<0.001). More than half of the midwives (53%) had concerns about the COVID-19 vaccine for the women in their care compared with 35% of doctors and 46% of midwifery students. Despite national guidelines recommending vaccination of breastfeeding women, 54% of practitioners were unlikely to recommend vaccination for this group. Conclusion This is the first study to explore the perceptions and intentions regarding COVID-19 vaccination from the perspective of those who receive and provide maternity care in Australia. Findings have utility to support targeted public health messaging for these and other cohorts.